2011
DOI: 10.1088/2040-8978/13/8/085201
|View full text |Cite
|
Sign up to set email alerts
|

Loss effects in the spectra of polarization modulational instability in weakly birefringent optical fibers

Abstract: We analyze the effects induced by material absorption in the spectra of polarization modulational instability in weakly birefringent optical fibers. We show that a large absorption of the pump wave may cause significant decreases of the growth of sidebands in the modulational instability process. This drop of gain is accompanied by a drift of the sideband frequencies. We demonstrate a technique for suppressing these frequency drifts, which is based on the use of fiber systems having a dispersion and a birefrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Optical fibers have been used as a mode of transmission of these photons in most QKD commercial applications [7]. Unfortunately, optical fibers undergo some slow fluctuations in the birefringence, and this can be modeled as a collective-noise [8,9]. As a result, avoiding noise in the communication process is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Optical fibers have been used as a mode of transmission of these photons in most QKD commercial applications [7]. Unfortunately, optical fibers undergo some slow fluctuations in the birefringence, and this can be modeled as a collective-noise [8,9]. As a result, avoiding noise in the communication process is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of group velocity mismatch (GVM) on MI was reported by Drummond et al [21] and showed that the MI process gradually decreases as GVM decreases and vanishes as GVM becomes zero. The detailed investigation of MI for single and dual pump has been reported [22,23]. In parallel, pump photons launched into different spatial modes give rise to intermodal MI (IM-MI).…”
Section: Introductionmentioning
confidence: 99%